Human Mesenchymal Stem Cell Grafts Enhance Normal and Impaired Wound Healing by Recruiting Existing Endogenous Tissue Stem/Progenitor Cells. (21st December 2012) - Shin, Laura; Peterson, Daniel A.
Abstract : This study evaluated the relative contribution of grafted human mesenchymal stem cells (hMSCs) and host stem/progenitor cells in promoting wound healing by using a novel asymmetric wound model in normal and impaired healing diabetic ( db/db ) mice to discriminate between the effect of direct engraftment and the subsequent systemic response. Grafted hMSCs significantly improved healing in both normal and impaired healing animals; produced significant elevation of signals such as Wnt3a, vascular endothelial growth factor, and platelet‐derived growth factor receptor‐α; and increased the number of pre‐existing host MSCs recruited to the wound bed. The study validates that hMSCs evoke a host response that is clinically relevant, and it is suggested that therapeutic efforts should focus on maximizing the mobilization of host MSCs. Abstract : Mesenchymal stem cells (MSCs) have been investigated as a clinical therapy to promote tissue repair. However, the disappearance of grafted cells soon after engraftment suggests a possible role as initiators of repair rather than effectors. We evaluated the relative contribution of grafted human MSCs and host stem/progenitor cells in promoting wound healing by using a novel asymmetric wound model in normal and impaired healing diabetic ( db/db ) mice to discriminate between the effect of direct engraftment and the subsequent systemic response. Experimental animals received paired wounds, with one wound receiving human mesenchymal stem cells (hMSCs) and the other wound receiving vehicle to assess local and systemic effects, respectively. Control animals received vehicle in both wounds. Grafted hMSCs significantly improved healing in both normal and impaired healing animals; produced significant elevation of signals such as Wnt3a, vascular endothelial growth factor, and platelet‐derived growth factor receptor‐α; and increased the number of pre‐existing host MSCs recruited to the wound bed. Improvement was also seen in both the grafted and nongrafted sides, suggesting a systemic response to hMSC engraftment. Healing was enhanced despite the rapid loss of hMSCs, suggesting that mobilizing the host response is the major outcome of grafting MSCs to tissue repair. We validate that hMSCs evoke a host response that is clinically relevant, and we suggest that therapeutic efforts should focus on maximizing the mobilization of host MSCs.